WATER QUALITY OF YAMUNA RIVER AT PRAYAGRAJ, U.P., INDIA - Nath, Satyendra; Pandey, Jigyasa; Nath, Shailendra; Sam, Sapna; Masih, Shalini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rivers are an essential part of our biosphere which is essential for the overall development of the present civilization. The present study was carried out to analyze the water quality at selected sites of river Yamuna in Prayagraj (Allahabad) city during January 2019 to May 2019. Samples were collected and analyzed for assessing the water quality characteristics as pH, turbidity, alkalinity, Ca 2+ hardness, Mg 2+ hardness, Cl- and Sulpate. The obtained results were compared to the standards limits of BIS. Analysis results showed that pH, turbidity, alkalinity, sulphate, Chloride of water was found within the permissible limits while Calcium and magnesium hardness values are higher than the permissible limits of BIS standards. The possible causes of deteriorating of Yamuna water due to discharged of untreated water and other human activity.